Bridging Soft Skills and Employability: The Mediating Role of Internship Practices in Developing Future Hospitality Talents - Penggalih, Gibran Bening; Hakim, Abdurrahman (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose – This study aims to examine the influence of soft skills on hospitality students’ employability skills, with internship practices acting as a mediating variable.    Design/methodology/approach –  This study employs a quantitative explanatory research design using survey data from 150 hospitality students and alumni of Indonesian universities. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to test the direct and mediating effects among variables.   Findings – The results show that soft skills have a positive and significant effect on both internship practices and employability skills. In addition, internship practices significantly mediate the relationship between soft skills and employability skills, indicating that practical work experience strengthens the transformation of soft skills into employability competencies.   Originality/value – This study contributes to hospitality education and employability literature by integrating internship practices as a mediating mechanism that links soft skills to employability outcomes. The findings provide practical implications for higher education institutions in designing curricula that strengthen both soft skills development and structured internship experiences to improve graduate work readiness.